SEC issues guidance on business continuity planning for registered investment companies. Issue 4 (7th November 2016) - McCarthy, Diana; Gordon, Kay
Abstract : Purpose: To explain guidance from the US Securities and Exchange Commission (SEC) Division of Investment Management concerning registered investment companies' business continuity and transition plans (BCPs). Design/methodology/approach: Discusses the SEC's concerns with fund complexes' operational complexity and reliance on technology and third-party service providers, lists notable practices in the BCPs of some registered fund complexes, and addresses practical considerations. Findings: While the SEC staff recognizes that it is not possible for a fund complex to anticipate or prevent every business continuity event, the staff also believes that fund complexes' preparedness would be enhanced if in addition to complying with the federal securities laws, fund complexes and their advisers consider additional factors related to BCPs discussed in the Guidance. Practical implications: It would be prudent for the fund boards to consider discussing the Guidance with fund investment advisers and fund CCOs to determine the status of fund complex BCPs and any gaps related to the Guidance. Boards may also want to review with their counsel the current BCP reporting framework and any enhancements needed in light of the Guidance. Originality/value: Practical guidance from experienced securities, fund management, regulatory and compliance lawyers.